Cases in marketing management / Luiz Moutinho - Moutinho, Luiz (Addison-Wesley, 1995)
This book helps students to develop essential marketing experience and skills by casting them in the role of the decision maker. Each case recreates situations confronting the Marketing Manager and, in the course of analysis and solution of problems, illustrates the integral process and techniques.